Sign language mobile apps: a systematic review of current app evaluation progress and solution framework - Dianes A/P David Emmanuel, Abdullah Hussein Abdullah Al-Amoodi, Salem Abdullah Salem Garfan (Tanjung Malim, 2024)
Sign language mobile apps: a systematic review of current app evaluation progress and solution framework by Dianes A/P David Emmanuel, Abdullah Hussein Abdullah Al-Amoodi, Salem Abdullah Salem Garfan